2015
DOI: 10.1097/bpo.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Perthes Disease

Abstract: Physicians should recommend the HONcode seal to their patients as a reliable indicator of Web site quality or, better yet, refer patients to sites they have personally reviewed. Supplying parents with a guide to health information on the Internet will help exclude Web sites as sources of misinformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
6
7
0
Order By: Relevance
“…This is in accordance to former studies on benign diseases [17-19]. A study on Spanish web pages on PCa showed that 31% of cancer web pages displayed quality seals, 62% provided adequate references, and 54% offered information on the last update [12].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This is in accordance to former studies on benign diseases [17-19]. A study on Spanish web pages on PCa showed that 31% of cancer web pages displayed quality seals, 62% provided adequate references, and 54% offered information on the last update [12].…”
Section: Discussionsupporting
confidence: 62%
“…In our study, only a minority of the web pages showed such a certification. In a similar study on Perthes disease, a comparable low number of the web pages had a HON certificate [17]. In a study on the 13 most frequently used web pages on PCa, Borgmann et al [14] found a slightly higher number of pages with HON certificate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pediatric practice adds an additional dimension of intensity as the patient’s parents diligently research their physicians or look for support from other parent/patient experiences. Up to 89% of parents of children with chronic disease are noted to search the Internet for information (4). …”
Section: Introductionmentioning
confidence: 99%
“…Increased accessibility and speed of communication have significantly altered the distribution of information on the internet for health issues [9]. As healthcare providers learn how to enhance shared decision-making and patient engagement, they have to acknowledge that patients are turning towards online sources for information.…”
Section: Discussionmentioning
confidence: 99%